Talking Human Rights: How social movement activists are constructed and constrained by human rights discourse - LANDY, DAVID (My University, 2013)
Human rights discourse is central for the work of international social movements. Viewing human rights as a context-dependent and socially constructed discourse, this article investigates how it is used by a specific social movement ? Israel-critical diaspora Jewish activists ? and argues that it can simultaneously challenge and reproduce existing practices of domination. The article applies contemporary critiques of human rights to the case of Palestine, where this discourse has arguably been used to undermine Palestinians? political subjectivity and collective struggle, and legitimise outside intervention. Nevertheless, transnational groups critical of Israel, particularly diaspora Jewish organisations, rely on a human rights frame. There are several reasons for this: it offers activists a means to achieve `cognitive liberation?, to speak about the issue and to frame their activities so as to attract recruits. The article investigates this paradoxical role of human rights, and recommends understanding it as a language which both constrains and enables the practice of transnational solidarity.
PUBLISHED
Keywords: human rights; social movements; Israel/Palestine; social constructivism; transnationalism; Diaspora Jews; human rights; Israel/Palestine; social movements; Diaspora Jews